2020
DOI: 10.3390/biomedicines8070200
|View full text |Cite
|
Sign up to set email alerts
|

Secreted Factors from Keloid Keratinocytes Modulate Collagen Deposition by Fibroblasts from Normal and Fibrotic Tissue: A Pilot Study

Abstract: Interactions between keratinocytes and fibroblasts in the skin layers are crucial in normal tissue development, wound healing, and scarring. This study has investigated the role of keloid keratinocytes in regulating collagen production by primary fibroblasts in vitro. Keloid cells were obtained from removed patients’ tissue whereas normal skin cells were discarded tissue obtained from elective surgery procedures. Fibroblasts and keratinocytes were isolated, cultured, and a transwell co-culture system w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Efforts to target and suppress fibroblasts in keloids have led to strategies such as regulating fibroblasts for scarless wound healing ( Zou et al., 2021 ) or inhibiting keloid-derived fibroblast growth and migration with LY2109761 ( Wang et al., 2021 ). In tandem, keratinocytes secrete factors that modulate fibroblast collagen production ( Alghamdi et al., 2020 ), and mast cells play an important role in dermal scarring ( Ud-Din et al., 2020 ) by interacting with fibroblasts in epithelial growth and regeneration ( Artuc et al., 2002 ). Bulk deconvolution showed unsurprising increases in fibroblasts, endothelial cells, and M2 macrophages/dendritic cells in keloid skin.…”
Section: Discussionmentioning
confidence: 99%
“…Efforts to target and suppress fibroblasts in keloids have led to strategies such as regulating fibroblasts for scarless wound healing ( Zou et al., 2021 ) or inhibiting keloid-derived fibroblast growth and migration with LY2109761 ( Wang et al., 2021 ). In tandem, keratinocytes secrete factors that modulate fibroblast collagen production ( Alghamdi et al., 2020 ), and mast cells play an important role in dermal scarring ( Ud-Din et al., 2020 ) by interacting with fibroblasts in epithelial growth and regeneration ( Artuc et al., 2002 ). Bulk deconvolution showed unsurprising increases in fibroblasts, endothelial cells, and M2 macrophages/dendritic cells in keloid skin.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, keloid keratinocytes appear to decrease collagen production by keloid fibroblasts. The authors suggested that signaling in both keratinocytes and fibroblasts is disrupted in keloid pathology (for more details about this article, see [ 9 ]).…”
Section: Cellular Mechanisms Epigenetic Modification and Proposed Therapies In Keloidsmentioning
confidence: 99%
“…Keloids are fibrotic skin diseases that occur at areas with a cutaneous injury. They typically extend beyond boundaries of the original wound (1)(2)(3)(4)(5)(6)(7)(8). They are characterized by excessive collagen deposition and abnormal cellular proliferation (5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…They typically extend beyond boundaries of the original wound (1)(2)(3)(4)(5)(6)(7)(8). They are characterized by excessive collagen deposition and abnormal cellular proliferation (5)(6)(7)(8)(9). Keloids can be pruritic near the site of injuries.…”
Section: Introductionmentioning
confidence: 99%